The Effectiveness of Discovery Learning Model on Students’ Writing Skills at Vocational High School Diponegoro Losari - Sofwatunnisa, Putri; Umaemah, Amroh; Waloyo, Edy (Jurnal Global Ilmiah, 2024)
This study investigates the impact of the discovery learning model on the writing skills of eleventh-grade students at Vocational High School Diponegoro Losari. The research used a One Group Pretest-Posttest Design and analyzed performance test scores before and after the implementation of the model. The results showed that students with the discovery learning model scored significantly higher in their analytical exposition text writing skills, with an average score of 76.66 compared to 36-45% before the model. The study also found that the use of the discovery learning model significantly improved the students' analytical exposition text writing skills.